Jews and Jewish identities in Latin America : historical, cultural, and literary perspectives - Bejarano, Margalit; Harel, Yaron; Topel, Marta F.; Yosifon, Margalith (Jewish Latin American studies, 2017)
"This collection of articles constitutes a major contribution to the growing field of Latin American Jewish studies, offering different perspectives on the rich and complex phenomena in the social, political, and cultural development of Jewish communities in the area. The essays span across a wide range of subjects, from comparisons between Jewish communities from different countries and with different levels of assimilation, the effects of globalization and transnationalism on the field, the interactions between Jews and non-Jews in the area, all the way to literary criticism. Based on an international conference organized by the University of Sao Paulo, the Dahan Center of Bar Ilan University, and the Academic College in Ashkelon, this volume offers a new approach to Latin American Jewish studies: it contributes to demystifying stereotypes and raising awareness of the importance of Latin America in a global context, and it highlights the relevance of the different Jewish communities across the globe in their special relationship to the state of Israel"--Back cover.